Hypercarbic cardiorespiratory reflexes in the facultative air-breathing fish jeju (Hoplerythrinus unitaeniatus): the role of branchial CO2 chemoreceptors - Boijink, Cheila de Lima; Florindo, Luiz Henrique [UNESP]; Costa Leite, Cleo A.; Kalinin, Ana Lucia; Milsom, William K.; Rantin, Francisco Tadeu (Company of Biologists Ltd, 2010)
The aim of the present study was to determine the roles that externally versus internally oriented CO2/H+-sensitive chemoreceptors might play in promoting cardiorespiratory responses to environmental hypercarbia in the air-breathing fish, Hoplerythrinus unitaeniatus (jeju). Fish were exposed to graded hypercarbia (1, 2.5, 5, 10 and 20% CO2) and also to graded levels of environmental acidosis (pH similar to 7.0, 6.0, 5.8, 5.6, 5.3 and 4.7) equal to the pH levels of the hypercarbic water to distinguish the relative roles of CO2 versus H+. We also injected boluses of CO2-equilibrated solutions (5, 10 and 20% CO2) and acid solutions equilibrated to the same pH as the CO2 boluses into the caudal vein (internal) and buccal cavity (external) to distinguish between internal and external stimuli. The putative location of the chemoreceptors was determined by bilateral denervation of branches of cranial nerves IX (glossopharyngeal) and X (vagus) to the gills. The data indicate that the chemoreceptors eliciting bradycardia, hypertension and gill ventilatory responses (increased frequency and amplitude) to hypercarbia are exclusively branchial, externally oriented and respond specifically to changes in CO2 and not H+. Those involved in producing the cardiovascular responses appeared to be distributed across all gill arches while those involved in the gill ventilatory responses were located primarily on the first gill arch. Higher levels of aquatic CO2 depressed gill ventilation and stimulated air breathing. The chemoreceptors involved in producing air breathing in response to hypercarbia also appeared to be branchial, distributed across all gill arches and responded specifically to changes in aquatic CO2. This would suggest that chemoreceptor groups with different orientations (blood versus water) are involved in eliciting air-breathing responses to hypercarbia in jeju.
Keywords: gills; cardiorespiratory control; hypercarbia; CO2 and H+ chemoreceptors; air breathing; jeju; Hoplerythrinus unitaeniatus